Enhanced ionic conductivity of scandia-ceria-stabilized-zirconia (10Sc1CeSZ) electrolyte synthesized by the microwave-assisted glycine nitrate process. Issue 11 (1st August 2017) - Azim Jais, Abdul; Muhammed Ali, S.A.; Anwar, Mustafa; Rao Somalu, Mahendra; Muchtar, Andanastuti; Wan Isahak, Wan Nor Roslam; Yong Tan, Chou; Singh, Ramesh; Brandon, Nigel P.
Abstract: Scandia-stabilized-zirconia is a potential zirconia-based electrolyte for intermediate temperature solid oxide fuel cells (IT-SOFCs). In this study, the properties of zirconia co-doped with 10 mol% Sc and 1 mol% Ce (scandia-ceria-stabilized-zirconia, 10Sc1CeSZ) electrolyte synthesized by the microwave-assisted glycine nitrate process (MW-GNP) were determined. The effects of microwave heating on the sintering temperature, microstructure, densification and ionic conductivity of the 10Sc1CeSZ electrolyte were evaluated. The phase identification, microstructure and specific surface area of the prepared powder were investigated using X-ray diffraction, transmission electron microscopy and the Brunauer-Emmett-Teller technique, respectively. Using microwave heating, a single cubic-phase powder was produced with nanosized crystallites (19.2 nm) and a high specific surface area (16 m 2 /g). It was found that the relative density, porosity and total ionic conductivity of the 10Sc1CeSZ electrolyte are remarkably influenced by the powder processing method and the sintering temperature. The pellet sintered at 1400 °C exhibited a maximum ionic conductivity of 0.184 S/cm at 800 °C. This is the highest conductivity value of a scandia-stabilized-zirconia based electrolyte reported in the literature for this electrolyte type. The corresponding value of the activation energy of electrical conductivity was found to be 0.94 eV in the temperature range of 500–800 °C. Overall, the use of microwave heating has successfully improved the properties of the 10Sc1CeSZ electrolyte for application in an IT-SOFC.